Analysis of advertisements of infant food commercialized in the city of Natal, Rio Grande do Norte, Brazil - Maria Giovana Binder Pagnoncelli; Almária Mariz Batista; Michelle Cristine Medeiros Da Silva; Ana Paula Marques Da Costa; Fábio Resende De Araújo; Marcela Pinheiro Marques; Cláudia M. De Quelhas Fidalgo; Maria Cleide Ribeiro Dantas de Carvalho (Universidade de São Paulo, 2009)
The advertising about maternal milk substitutes has been pointed as one of the factors responsible for the breastfeeding low rates. In this way, legal support was created to assure that the use of such products would not interfere on the healthy breastfeeding habit of the population. This study, developed between June 2006 and May 2008 in the city of Natal, state of Rio Grande do Norte, analyzed the food advertisements divulged under the validity of Law # 11.265/2006, which controls in Brazil the food commercialization and the publicity addressed to parents or keepers of nursling and children in the first childhood. 220 advertisements, being 141 of technical-scientific nature, and 79 for strictly commercial promotion, were collected and evaluated according to legal requirements. The results from this analysis showed that 100% of the advertisements of technical-scientific nature overstepped the clause V; 18.4% the clause IV and 14.2% the clauses I, II and III of article 19th of Law # 11265/2006. In 42% of the advertisements strictly for commercial promotion, the mandatory information mentioned at clauses I and II of the article 5th were not shown. In 8.7% of the advertisements containing such information, it was placed in an area that embarrassed its identification and reading, due to used fonts size and/or color; similarly as occurred with the information required by article 19th, in the advertisements of technical-scientific nature. A propaganda de substitutos do leite materno tem sido apontada como um dos fatores responsáveis pelos baixos índices da amamentação. Neste sentido, dispositivos legais foram criados para assegurar o uso desses produtos, sem que haja interferência no aleitamento materno. Este estudo objetivou analisar propagandas de alimentos abrangidos pela Lei nº 11.265/2006, que regulamenta a comercialização e publicidade de alimentos para lactentes e crianças de primeira infância no Brasil, no período de junho 2006 a maio de 2008, na cidade de Natal/RN. Foram coletadas 220 propagandas, sendo 141 de material técnico-científico e 79 de promoção comercial que foram avaliadas quanto às exigências legais. O resultado desta análise demonstrou que 100% das propagandas veiculadas em material técnico-científico infringiram o inciso V; 18,4% o inciso IV e 14,2% os incisos I, II e III do artigo 19 da Lei nº 11.265/2006. Em 42% das promoções comerciais não foram veiculadas as informações obrigatórias constantes dos incisos I e II do artigo 5º. Em 8,7% das que continham essas informações, estas estavam postas em local que dificultava sua identificação e leitura devido ao tamanho e cor das letras, semelhantemente ao ocorrido com as informações exigidas pelo artigo 19 nas propagandas veiculadas em material técnico-científico.